Risk Factors Affecting The Incident Of Preeclamsia In Klambu Health Center, Grobogan District - Musdalifah, Ulfah; Indah Rahmawati, Mei; Fajrin, Rafika; Suwanti, Suwanti (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2025)
Preeclampsia is a collection of symptoms that occur during pregnancy, childbirth and the postpartum period including hypertension, edema and proteinuria, symptoms usually appear after 20 weeks of gestation or more. There were 19 cases of visits by TM III pregnant mothers who had ANC at the Klambu Community Health Center with preeclampsia, in 2021 there were 24 cases and in 2022 there were 38 cases. From year to year visits by mothers with preeclampsia have increased. The aim of the research was to determine the risk factors that influence the incidence of preeclampsia at the Klambu Community Health Center, Grobogan Regency. The research method used a case control design, the research was conducted in October 2023 with a population of all pregnant women aged 35 weeks to 40 weeks with preeclampsia in 2022, there were 38 people. The samples in this research used a 1:1 ratio so that the number of case samples was 38 and the number of control samples was 38, so there were a total of 76 samples. Data analysis uses the Odds Ratio test. The research results show that the age of most mothers is not at risk, between 20-35 years 75%, the parity of mothers is not at risk or multipara 64.5%, the nutritional status based on LILA is not normal or <23.5cm and >25cm 72.4%, the pregnancy interval is not at risk or >2 years 59.2%, no history of hypertension 89.5, history of standardized ANC 90.8% and mother's education at risk or elementary/middle school graduate education 57.9%. Risk factors for preeclampsia include maternal age (OR=1.528), nutritional status (OR=1.487), history of hypertension (OR=2.267) and ANC (OR=1.373). Protective factors for preeclampsia include parity (OR=0.708), pregnancy spacing (OR=0.721) and maternal education (OR=0.415). It is hoped that midwives will be able to improve the quality of midwifery services related to ANC and early detection of preeclampsia related to the risk factors of pregnant women's age, nutritional status of pregnant women and history of hypertension.